Advances in epigenetic studies of plant cadmium stress - Gao, Yonggang; Wang, TZufeng; Zhao, Cheng (Frontiers in Plant Science, 2025)
As the global population continues to grow, achieving ecological sustainability and ensuring food production have become urgent challenges. Among various environmental stresses, heavy metals, particularly cadmium (Cd), pose a significant threat to plant growth and development. Breeding cadmium-resistant crop varieties that minimize Cd accumulation is therefore crucial for promoting sustainable agriculture. In response to Cd stress, plants undergo a series of regulatory mechanisms, including DNA methylation, chromatin remodeling, and histone acetylation, to mitigate cellular damage. Understanding the epigenetic responses of plants to cadmium stress is a key research area that holds substantial significance for both agriculture and environmental biology. This article reviews the current research on plant responses to cadmium stress and the underlying mechanisms of their epigenetic responses, aiming to provide theoretical insights for analyzing the epigenetic mechanisms of heavy metal stress in major crops. We can leverage genomics, single-cell sequencing, stereo-seq, and other advanced technologies in conjunction with epigenomics, plant genetics and molecular biology techniques to conduct comprehensive and in-depth studies on the epigenetic changes that occur in plants following Cd exposure. Systematically elucidating the molecular mechanisms by which plants perceive and respond to Cd stress will aid in the development of more effective bioremediation strategies for heavy metal-contaminated soils and facilitate.